Sex-Related Differences in Hip Kinematics During General Movements in Early Infancy: A Biomechanical Cross-Sectional Study - Lucía Fernanda Flores-Santy; Barbara Martina Trujillo Gutiérrez; Cristina Mileny Campaña Iza; Juan Pablo Hervás Pérez (Children)
The General Movements Assessment provides early insight into motor development’s range of motion; however, its relationship with joint kinematics, such as hip abduction range of motion, remains underexplored. This study analyzed hip abduction kinematics during General Movements, evaluating potential sex differences and variations in movement patterns (Fidgety vs. Writhing), and aimed to provide quantitative data that complement qualitative pediatric assessments. This cross-sectional observational study analyzed video recordings of spontaneous motor activity in 32 infants under three months of corrected age. Hip abduction range of motion was extracted using biomechanical analysis during General Movements. Interrater reliability was evaluated using Fleiss’s Kappa. Correlations were assessed using Pearson’s test, and a two-way ANOVA examined the effects of sex and the type of movements on range of motion. Interrater reliability for movement classification was excellent (Kappa = 0.909, p < 0.001). No significant correlations were found between sex or General Movements type and hip abduction range of motion (p > 0.68). Two-way ANOVA showed no significant effects of sex, movement pattern, or their interaction on range of motion in either hip (right: p = 0.726, left: p = 0.823), with small effect sizes (η2 < 0.013). A minor asymmetry favoring the right hip was observed but was not clinically significant. Sex and General Movements type did not significantly influence hip abduction range of motion in infants under three months. Early joint mobility appears consistent across sexes and movement patterns, supporting its reliability as a biomechanical marker of typical development.